Parenting behaviors and deviant peer affiliation among Chinese adolescents: the mediating role of psychological reactance and the moderating role of gender - Chunmei Zhang; Ying Luo; Ronghua Zhang (BMC Psychology)
Abstract Given the negative impact of deviant peer affiliation on adolescent behavioral development, understanding its underlying mechanisms is essential. Drawing on social development model, psychological reactance theory and adolescent-limited delinquency theory, this study examined the relationship between parenting behaviors and adolescents’ deviant peer affiliation, as well as the mediating role of reactance and the moderating role of gender. The research involved 1,822 high school students (M age = 15.28 years, SD age = 2.40) from two provinces in China. All students completed a face-to-face questionnaire administered in a computer room at their respective school. This study found that parental emotional warmth was negatively correlated with adolescent deviant peer affiliation. On the contrary, parental rejection and overprotection were positively correlated with adolescent deviant peer affiliation. Furthermore, the findings indicated that reactance significantly mediated the relationship between parental emotional warmth, rejection, overprotection, and deviant peer affiliation, with reactance fully mediating the relationship between parental overprotection and deviant peer affiliation. Finally, the gender of the adolescent was found to significantly moderate the relationship between parental rejection (β = -0.10, p =.04), emotional warmth (β = 0.16, p =.003) and deviant peer affiliation, although no moderation was observed regarding parental overprotection. These results suggest that various parenting behaviors employ complex mechanisms to influence adolescents’ deviant peer affiliation, with reactance and gender differences playing pivotal roles. This study offers new insights into the mechanisms underlying adolescent deviant peer affiliation and underscores the importance of reducing deviant peer affiliation through interventions targeting reactance and parenting behaviors.